Problem-Based Learning: Alternative Learning Model to Improve Students’ Critical Thinking Ability - Adeliana, F; Sintawati, Mukti; Anggara, Rizki (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The goal of this study was to help fourth-grade children improve their critical thinking skills. This is a Classroom Action Research project. The study was divided into two cycles, each of which included planning, action, observation, and reflection. Muhammadiyah Notoprajan Elementary School fourth grade pupils were used as research subjects. The ability to think critically in mathematics is the focus of this study. The test was utilized as a means of gathering information. The descriptive analysis was employed in the data analysis. The findings of the study show that after learning with PBL, students' mathematics learning outcomes improve. From the first to the second cycle, the percentage of students who received the KKM grew from 42.85% to 78.57%. The findings also demonstrate that using the PBL paradigm in the classroom can help fourth-graders enhance their critical thinking skills. This can be observed in the percentage of pupils in the high group with weak critical thinking skills, which was 62.40% in the first cycle and increased to 77.40%in the second cycle. Because the student sheet given to students in this study was in accordance with the PBL syntax and provided ill-structured issues as a starting point at the beginning of learning, there was an increase. Students can use the PBL syntax in student sheet to address problems that aren't well-structured.